HPLC and FTIR analysis of phytochemicals and antioxidants of Aloe vera exposed to petroleum hydrocarbons and remediation treatments with organic and inorganic amendments - Sarah Alharthi; Ola A. Abu Ali; Amal A. Alyamani; Nashi K. Alqahtani; Rokayya Sami; Uguru Hilary; Idisi Benjamin Evi; Akpokodje Ovie Isaac; Haneen H. Mouminah; Norah E. Aljohani; Mahmoud Helal; Salma M. Aljahdali; et al. (PLoS ONE, 2026)
Environmental pollution has become a major threat to public safety, and the integrity of bioactive compounds in medical plants. This investigation was conducted to assess the consequence of petroleum hydrocarbons contamination, on the nutritional and medicinal qualities of Aloe vera (L.), and to evaluate the efficiency of the various remediation strategies. During the study, soil contaminated with 20% crude oil (petroleum), was treated with five different treatments (T1 to T5), which consist of different concentrations of organic manure, potassium permanganate, and improved seaweed extract manure. All the laboratory tests were conducted by following standard procedures. Specifically, high performance liquid chromatography (HPLC), was used to measure the concentrations of vitamins A and E, as well as the acemannan and aloin, while the Fourier transform infrared spectroscopy (FTIR) analysis, was utilized to evaluate the presence petroleum hydrocarbons inside the extract. The results revealed that, the petroleum contamination and treatment strategies have significant influence, on the extract’s phytochemicals and the antioxidant activity behavior. The extract vitamins A, C and E concentrations varied from 7.68 to 12.47 mg/kg, 1323.67 to 2116 mg/kg, and 54.30 to 73.28 mg/kg, respectively. Additionally, TPC and TFC level of extract varied from 30.15 to 78.50 mg GAE/g, and 9.51 to 38.01 mg QE/g, respectively. The Treatment 4 unit (OM + ISE) showed the best remediation performance, with the highest essential bioactive compounds recovery rates. This affirmed that seaweed extract and organic matters are potential eco-friendly materials, with high efficacy in alleviating the harmful effects, associated with petroleum toxicity on medical plants. This will lead to maximization of the therapeutic benefits of Aloe vera plant, grown in petroleum contaminated environment, thus guaranteeing public safety.